2022
DOI: 10.3390/sym15010016
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Radiative Darcy–Forchheimer Flow of Cu/Ag Nanoliquid in Water Past a Heated Stretchy Sheet with Magnetic and Viscous Dissipation Impacts

Abstract: This communication predominately discusses the rheological attributes of the Darcy–Forchheimer flow of a nanoliquid over a stretchy sheet with a magnetic impact. The present model considers the two diverse nanoparticles, such as Cu and Ag, and water as a base liquid. The heat equation accounts for the consequences of thermal radiation and a nonlinear heat sink/source when evaluating heat transmission phenomena. The current mechanical system is represented by higher-order PDEs, which are then remodeled into non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…A few processes are turbojets, flm cooling, gas turbines, mass transfer cooling, and a plethora of additional technologies that fall under this category. Divya et al [21] inquired about the fow of H 2 O based Cu/Ag nanoparticles past a heated SS with suction/ injection. Tey reported that the SFC decays when improving the SI parameter.…”
Section: Introductionmentioning
confidence: 99%
“…A few processes are turbojets, flm cooling, gas turbines, mass transfer cooling, and a plethora of additional technologies that fall under this category. Divya et al [21] inquired about the fow of H 2 O based Cu/Ag nanoparticles past a heated SS with suction/ injection. Tey reported that the SFC decays when improving the SI parameter.…”
Section: Introductionmentioning
confidence: 99%